FISIOTERAPIA NO CONTEXTO ESCOLAR: PROPOSTA DE ATIVIDADES PARA ESTIMULAÇÃO EM GRUPOS - Sacon, Alana B.; Pretto, Luciana M.; Bonamigo, Elenita C. B.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo